Artificial Intelligence dan Pertanggungjawaban Pidana dalam Perspektif Hukum Islam: Studi atas Konsep Taklif dalam Fiqh Jinayah - Izazi, Muammar (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2025)
This study aims to examine the possibility of criminal liability for Artificial Intelligence (AI) from the perspective of Islamic law through an analysis of the concept of taklif in fiqh jinayah (Islamic criminal jurisprudence). As the use of AI increases across various sectors of life, fundamental questions arise regarding the legal status of AI when it causes harm or engages in criminal acts. In Islamic law, taklif is a fundamental requirement for legal accountability, presupposing intellect, free will, and the ability to distinguish between right and wrong—attributes that AI does not possess. This research employs a qualitative juridical-normative approach using the library research method, analyzing classical primary sources in fiqh jinayah, as well as applying the maqasid al-shariah approach as a normative analytical framework. The findings indicate that although AI does not meet the criteria of a mukallaf, Islamic legal principles such as daman (liability) and al-‘amal bil wasait (liability through intermediaries) provide a basis for attributing legal responsibility to developers, controllers, or users of AI. The maqasid al-shariah approach further strengthens the legitimacy of legal reasoning (ijtihad) concerning non-human entities in order to preserve public interest (maslahah) and prevent harm (mafsadah). This study emphasizes the importance of reconstructing Islamic law to ensure its adaptability in response to the rapid development of digital technologies.